THE DIGNIFIED JUSTICE PERSPECTIVES ON THE ENIGMA OF HEALTH PROTOCOLS COVID-19 AS A CODE OF ETHICS - Ermanto Fahamsyah; Fradhana Putra Disantara (Jurnal Pembaharuan Hukum, 2022)
Ethics and law are often related to politics, not least in the Regional Head Election (Pemilukada). However, the implementation of legal and ethical relations in political dynamics is often a matter of debate, not a code of ethics. The purpose of this study is to examine aspects of the relationship between ethics and politics in terms of legal compliance, providing a study of the validity of the COVID-19 Health protocol as a code of ethics at regional head elections from the perspective of dignified justice. This legal research uses primary and secondary legal materials with a conceptual and statutory approach. The results of the study stated that from the point of view of legal compliance, the code of ethics is an element that should be applied in political life; because the code of ethics will encourage the participants of the Pemilukada to have three main characteristics, namely compliance, identification, and internalization. Then, the perspective of dignified justice assesses the position of the COVID-19 health protocol as a code of ethics as valid and relevant to legal practice, the concept of legal reform, and the general idea of the theory of dignified justice.